Optimization and spatial pattern of large-scale aquifer thermal energy storage. (1st January 2015) - Sommer, Wijbrand; Valstar, Johan; Leusbrock, Ingo; Grotenhuis, Tim; Rijnaarts, Huub
Highlights: Thermal interference limits large-scale application of ATES . Efficiency of large-scale ATES systems can be improved by better well placement. Economic benefits are mainly sensitive to storage temperatures and gas price. Abstract: Aquifer thermal energy storage ( ATES ) is a cost-effective technology that enables the reduction of energy use and CO2 emissions associated with the heating and cooling of buildings by storage and recovery of large quantities of thermal energy in the subsurface. Reducing the distance between wells in large-scale application of ATES increases the total amount of energy that can be provided by ATES in a given area. However, due to thermal interference the performance of individual systems can decrease. In this study a novel method is presented that can be used to (a) determine the impact of thermal interference on the economic and environmental performance of ATES and (b) optimize well distances in large-scale applications. The method is demonstrated using the hydrogeological conditions of Amsterdam, Netherlands. Results for this case study show that it is cost-effective to allow a limited amount of thermal interference, such that 30–40% more energy can be provided in a given area compared to the case in which all negative thermal interference is avoided. Sensitivity analysis indicates that optimal well distance is moderately insensitive to changes in hydrogeological and economic conditions. Maximum economic benefit compared to conventional heating and cooling systems on the other hand is sensitive, especially to changes in the gas price and storage temperatures.